(untitled) (Revista Apotheke, 2022)
We’d like to develop a reflection about the forms of performance of the performing arts teacher in multiple teaching environments, considering basic education as the focus. We performed a decoupage about the possible forms of performance of this teacher, here characterized by metaphors: artist teacher, actor teacher, stage director teacher and performer teacher. The role of the Performing Arts teacher requires flexibility and play, as most of the time, these professional finds himself in an expedient threshold of versatility: master-director-actor-artist; our field of experimentation has been the basic education where we find ourselves.